Metadata model for database query on dynamic database federation in data grid environment based on ontology framework : a text similarity approach - Adiyarta, Krisna; Salim, Naomi (Penerbit UTM Press, 2008)
One of the aims of the Grid is to promote the open publication of scientific data. If this is realized then it is expected that many of the advances to flow from the Grid will be from applications that combine information from multiple data sets. An investigation into the requirements of early Grid projects has concluded that the prospect exists for millions of data resources and petabytes of data being accessible in a Grid environment [22]. Support for federating data resources is therefore vital to the success of the Grid. Grid database federation requires a highly dynamic federation. It means that, Grid database should accept changes occur in a federated database. Therefore, database systems need metadata management that has a capability to organize and maintain stored information in term of a dynamic federation. In this paper we discuss our proposed of metadata management model that provide a dynamic framework for grid database federation. We present a model of metadata management in term of an ontology based data integration framework.